Revealing the characteristics and propagation patterns of hydrological drought in Sichuan using GNSS-based runoff estimates - Wei You; Zijian Liu; Zhongshan Jiang; Xinghai Yang; Miao Tang; Xiangyu Wan; Xinchun Yang (International Journal of Digital Earth)
Understanding hydrological drought is vital for effective disaster mitigation and management. However, challenges like sparse hydrological monitoring stations and data acquisition present significant obstacles for studying hydrological drought in specific regions. This study developed a Global Navigation Satellite System (GNSS) -based runoff index to assess the hydrological drought in Sichuan. Regional equivalent water height (EWH) was estimated using the vertical displacement of continuous GNSS stations based on Green's function method. Combining this with high-precision precipitation and evapotranspiration data, the runoff in Sichuan using the water balance equation, resulting in the standardized runoff index (SRI-GNSS) was calculated. The findings show that Sichuan’s hydrological drought duration varies from one to nine months, and SRI-GNSS indicates a trend towards hydrological wetness. The drought’s intensity remained stable at around 1.15, but its severity accumulated over longer periods. The transit from meteorological to hydrological drought took approximately two months, with a 48.4% propagation probability. Influences like the El Niño-Southern Oscillation, Pacific Decadal Oscillation and North Atlantic Oscillation significantly influenced SRI-GNSS variability during 2016–2018. This study addresses gaps in hydrological drought assessments based on runoff in Sichuan Province and highlights the potential of GNSS technology for advancing hydrological research in regions with limited runoff data.